Religious Tolerance and the Spirit of Pluralism: QS. Al-Kafirun in Buya Hamka’s Tafsir Al-Azhar - Misnatun Misnatun; Mohammad Ruslan; A. Ubaedillah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
Tolerance is an urgent necessity in a pluralistic society such as Indonesia. As a country rich in cultural, ethnic, and religious diversity, Indonesia faces potential threats of social conflict if harmony is not maintained. The unity and integrity of the nation are strongly influenced by how well its people can uphold peaceful coexistence, especially in matters of religious difference. In this context, the interpretations of Qur’anic exegetes (mufassir) like Buya Hamka become essential, considering that the majority of Indonesians are devout Muslims who respect the teachings of the Qur'an. This study aims to explore the concept of tasamuh (tolerance) as conveyed by Buya Hamka in his Tafsir Al-Azhar, specifically in the interpretation of Surah Al-Kafirun (verses 1–6), and its relevance to multicultural and pluralistic life in Indonesia. This research employs a qualitative library research method, collecting and analyzing literature from classical texts, books, journals, and other relevant sources. Data were then processed using content analysis to explore the values of tolerance embedded in Buya Hamka’s interpretation. The results reveal that Buya Hamka strongly emphasizes the importance of mutual respect and peaceful coexistence among people of different faiths. He argues that Surah Al-Kafirun upholds a firm yet respectful boundary between faiths—encouraging tolerance without promoting religious relativism. The findings contribute to the discourse on Islamic-based character education in Indonesia, reinforcing the message that pluralism should not be feared, but embraced with compassion and integrity.